Pengaruh Brand Ambassador, Brand Image, dan Event Marketing terhadap Purchase Decision Tiket Allo Bank Hangout Festival 2025: Studi pada Pengunjung di Wilayah Jabodetabek - Divani Mona Ritonga; Nadya Fadillah Fidhyallah; Daru Putri Kusumaningtyas (Indo Publishing, 2026)
This study aims to analyze the influence of brand ambassador, brand image, and event marketing on purchase decision of Allo Bank Hangout Festival 2025 tickets among visitors in the Jabodetabek area. The research employs a quantitative approach with a survey method involving 125 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that brand ambassador has a positive and significant effect on purchase decision (β = 0.444, t = 6.582, p < 0.001). Brand image also has a positive and significant effect on purchase decision (β = 0.285, t = 3.684, p < 0.001). Event marketing has a positive and significant effect on purchase decision (β = 0.212, t = 2.524, p = 0.012). Among the three variables, brand ambassador is the most dominant factor influencing purchase decision. These findings reinforce the theoretical concepts of celebrity endorsement, brand image, and experiential marketing in shaping consumer behavior, particularly in the event and entertainment industry. The study provides practical implications for digital banks and event organizers in designing more effective marketing strategies oriented toward consumer experience.